Technical and venographic variations in embolization of primary versus recurrent varicocele - Sultan R. Alharbi (Medicine, 2026)
Varicocele embolization is an established treatment for primary and recurrent varicoceles. However, technical outcomes and venographic patterns may differ depending on whether the varicocele represents a primary disease or a recurrence following prior surgery or embolization. This study compared technical performance and venographic characteristics across these clinical scenarios. We retrospectively reviewed 92 consecutive patients who underwent varicocele embolization at a single academic center between January 2021 and June 2023. Patients were stratified into 3 groups: primary varicocele (n = 43), recurrent varicocele after microsurgery (n = 42), and recurrent varicocele after prior embolization (n = 7). Technical success, venographic findings (including the presence of a patent refluxing internal spermatic vein and collateral channels), procedure time, radiation dose, and number of coils used were compared using the chi-square or Fisher exact tests for categorical variables and the Kruskal–Wallis test for continuous variables. Technical success was achieved in 100% of patients in both the primary varicocele and recurrent varicocele after microsurgery groups but was significantly lower in patients with recurrent varicocele after prior embolization (57%; P < .001). A patent refluxing internal spermatic vein was consistently present in the primary varicocele and recurrent varicocele after microsurgery groups but absent in the recurrent varicocele after prior embolization group ( P < .001). Venous collaterals were identified in 86%, 67%, and 100% of cases in the primary varicocele, recurrent varicocele after microsurgery, and recurrent varicocele after prior embolization groups, respectively ( P = .033). Procedure times differed significantly among groups ( P = .017), with median times of 18 minutes (interquartile range [IQR] = 15–28) for primary varicocele, 23 minutes (IQR = 18–30.3) for recurrent varicocele after microsurgery, and 31 minutes (IQR = 26.5–41.5) for recurrent varicocele after prior embolization. Radiation dose also differed significantly ( P = .03), with median doses of 131 mGy (IQR = 91.8–166.5), 120 mGy (IQR = 85.25–192), and 195 mGy (IQR = 151.5–207.5) in the respective groups. The number of coils used was comparable among groups (median 4 [IQR = 3–4]; P = .62). Recurrent varicocele demonstrates distinct venographic patterns depending on prior treatment modality. Recognizing these patterns may inform procedural planning and patient counseling in recurrent cases.